Les États-Unis à l’heure du choix. Entre conservatisme républicain et pragmatisme démocrate - Meriem Naili (Transatlantica)
Far from a mere partisan contest, the election of November 3, 2020 represented a moment of truth for a Republican presidency marked by the appearance and affirmation of “Trumpism” and a Democratic opposition on the path to structural and ideological reinvention ever since Donald Trump’s 2016 election. As the events of Minneapolis of May 25, 2020 and the passing of George Floyd revealed, America is in the thralls of a deep identity crisis. What are the options open to voters and, more importantly, what are the real issues that lie behind this historic election? At this historic juncture, this seminar gave us a dynamic presentation of the different perspectives and issues facing America today.